In vivo functional and health benefits of a prebiotic soursop whey beverage processed by high-intensity ultrasound: Study with healthy Wistar rats. (30th June 2022) - Guimarães, Jonas T.; Almeida, Patrícia P.; Brito, Michele L.; Cruz, Beatriz O.; Costa, Nathalia S.; Almeida Ito, Raphaela V.; Mota, Jéssica C.; Bertolo, Mirella R.V.; Morais, Sinara T.B.; Neto, Roberto P.C.; Tavares, Maria Inês B.; Souto, Felipe; et al.
Highlights: A prebiotic soursop whey beverage was processed by high-intensity ultrasound (HIUS). The in vitro bioactivities were tested to verify possible effects in vivo. Wistar rats were used in a feed intervention with sonicated and thermally treated beverages. The HIUS beverage decreased total triglycerides, vLDL-c and alanine aminotransferase (ALT). In vivo benefits were related to bioactive peptides and antidiabetic activity of HIUS beverage. Abstract: New technologies for food processing have been used to enhance the beneficial effects of foods. This study aimed to evaluate the effects of a prebiotic soursop whey beverage processed by high-intensity ultrasound (HIUS) on healthy rats. Whey beverages were processed by HIUS (20KHz, 520 W of nominal power, <53 °C, 20.3 W of acoustic power, energy density of 2.9 kJ.cm −3 and 9.5 min to process 100 mL) and high-temperature short-time (HTST, 75 °C for 15 s) before being supplemented to Wistar rats by gavage for 15 days. Antioxidant, antidiabetic, anti-hypertensive, and anticancer activities, lipid peroxidation, bioactive peptides, and microstructure of the beverages were analyzed. In addition, the body mass, food, and water intake, systolic blood pressure, biochemical and oxidative stress parameters were measured. The sonicated beverage induced satiety, decreased glutathione peroxidase activity, total triglycerides, very-low-density lipoprotein cholesterol, and alanine aminotransferase. These findings suggest that ultrasound technology can provide in vivo health and functional benefits.